Cultivating Organizational Resilience through Prophetic Leadership: Empirical Insights from Islamic Schools in the Volatile Post-Pandemic Era - Ach Hafsin; Sahudi Sahudi (STAI Syaichona Moh. Cholil Bangkalan, 2024)
This study explores the role of Prophetic Leadership in fostering organizational resilience within Islamic schools during the volatile post-pandemic era. Utilizing a qualitative phenomenological approach and a multi-site case study design, data were gathered through in-depth interviews, passive observations, and documentation analysis at several resilient Islamic institutions. The findings reveal that prophetic traits—Shiddiq (integrity), Amanah (accountability), Tabligh (communication), and Fathonah (intelligence)—collectively function as both a